Influence of Light Intensity on Lipid Productivity and Fatty Acids Profile of Choricystis sp. LBB13-AL045 for Biodiesel Production - Swastika Praharyawan; Delicia Yunita Rahman; Dwi Susilaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
The influence of various light intensity on the lipid productivity, fatty acids profile, and biodiesel properties of Choricystis sp. AL045 were examined. Choricystis sp. LBB13-AL045 was a high lipid content microalgal strain (up to 42.49 ± 0.41% per dry weight basis) with great performance of its growth (specific growth rate and biomass productivity were up to 0.802 ± 0.013 day-1 and 108.57 ± 8.07 mg L-1 day-1, respectively). Such results indicated its high lipid productivity and its potency to be used for biodiesel production. The treatment of various light intensities on the microalgal culture resulted obvious differences in lipid productivity and fatty acids composition. Maximum lipid productivity (46.13 ± 3.43 mg L-1 day-1) was at 405 µmol m-2 s-1 of light intensity. The fatty acids profiles of four light intensities treatments were quite similar; the major components of fatty acid obtained from Choricystis sp. LBB13-AL045 oil were oleic acid (C18:1) and palmitic acid (C16:0), which provided a strong indication of high-quality biodiesel. Biodiesel properties were determined by empirical equations and found to be within the limits of biodiesel standard SNI 7182:2015, ASTMD6751-08 and EN14214.